Birsay Bay, Orkney: Human exploitation of natural and agricultural resources - Morris, Christoper D.; Rackham, James (Hikuin, 1989)
The Bay of Birsay has been the focus of archaeological interest since the mid 19th Century, and in particular a number of campaigns took place on the Brough of Birsay, in the 1930s, 1950s and 1960s. Fromm1973 to 1982, renewed excavations took place on various sites around the Bay, including the Brough of Birsay. As might be expected, until this recent work, little attention had been paid to the recovery and analysis af ecofactual, as opposed to artefactual and structural data. Work on the excavation of Room 5 onn the Brough of Birsay introduced sieving techniques, which produced some interesting indications in analyses by specialists of what might be expected with more rigorous attention to economic and environmental data . Shortly before this excavation, Dr Anna Ritchie undertook an important “rescue” excavation on the site of a mound on the Point of Buckquoy, and in 1977, Mr John Hedges undertook a preliminary “rescue” excavation at Saevar Hove, on the Mainland side of the Bay. These are now published, and have included important analyses of the ecofactual data by relevant specialists. Similar analyses are in train for the material recovered from both the recent excavations on the Brough of Birsay, and those from the various excavations along the Brough Road and in Birsay Village.